Social cognitive career theory: A qualitative approach in Peruvian engineering female students - Ramos-Diaz J. (2018)
Within the rapid proliferation of gender studies and the underrepresentation of women in science, technology, engineering and mathematics (STEM), an area of research has emerged among scholars. Over the past years, different academic, health and economic institutions have called for a closer analysis of women underrepresentation in STEM careers. In Peru, there is some preliminary evidence with regard of women underrepresentation in STEM careers, however, qualitative studies are scarce in the field. To analyze this gender gap phenomenon, we explored experiences, feelings, behaviors and Social Cognitive Career Theory variables such as self-efficacy, barriers, supports and career development. To reach this goal, qualitative and in-depth interviews were carried out among female engineering students. All participants were in their last year of career andwere selected from three universities in Lima, Peru. A thematic analysis confirmed SCCT variables such as self- efficacy, interest, goals, outcome expectations, barriers and supports in different themes. In addition to this, several subthemes emerged in each component across the sample. However, it was of particular interest the presence of sub- themes in the barrier theme, which was composed of "economic barriers", "effects barriers", "mother career barriers", "father career barriers", "institutional barriers", "social barriers", "direct gender discrimination" and "indirect gender discrimination". Even though these factors were not present in the majority of students, it showed educational experiences in female students from engineering careers in Peru. Implications for these findings are discussed for educational institutions, career counsellors and gender equality policymakers.